Biological Aspects and Feeding Ecology of Sembilang Plotosus canius in Langsa Estuary - Agus Putra Abdul Samad; Nur Fazillah Nur Fazillah; Rindhira Humairani; Ilhamdi; Nan Fan Hua (HAYATI Journal of Biosciences, 2022)
The knowledge of the biological aspects and feeding activity of fish is required to manage the lack of data on fisheries. In this study, a total of 200 Plotosus canius were caught and examined to obtain information on their biological aspects, length-weight relationship, and feeding activity. The fish were captured using a gill net and traditional fishing trap called Bubu. Subsequently, all samples were examined for total body weight, total length, condition factor, gonad maturity, and feeding activity. The results showed that the specimens captured were 156 males and 44 females weighing between 95-280 gr and 117-214 gr with the length of 26-39 cm and 28-36.3 cm, respectively. The length-weight relationship showed a negative allometric growth pattern. The mean condition factors of males and females were 1.1048 and 1.0102, respectively. At the same time, the maturity level of gonads was at I and II. Moreover, it was discovered that most organisms in the digestive tract were shrimp, worms, small fish, and crabs, while the highest index of preponderance was in shrimp with 42%. In conclusion, this study showed the new information about length-weight, biological condition, and feeding habits of Plotosus canius, which can be inventoried to strengthen data on sustainable fisheries management.